Revolusi Teknologi dalam Efektivitas Pencegahan Kejahatan Laut: Sebuah Evaluasi terhadap Teknologi Canggih dalam Deteksi dan Penanggulangan Aktivitas Ilegal - Wijayanthi, Fatimah Ratna; Permatasari, Pita; Nugraha, Alvian (PT Elaborium Elevasi Indonesia, 2024)
Indonesia, as an archipelagic country with a strategic geographical position, faces complex maritime security challenges amid advancements in information technology and globalization. This study aims to evaluate the potential and challenges of integrating advanced technology in detecting and preventing maritime crimes. A qualitative research method was employed by collecting data from relevant legal sources and applying a deductive approach. The results indicate that, although advanced technologies such as remote sensing and automation offer significant potential in enhancing maritime surveillance, there are substantial challenges, including the effectiveness of technology, accessibility, and related legal aspects. Collaboration between agencies and the integration of technology in maritime security strategies are deemed essential to address these challenges. In confronting this, Indonesia focuses on developing a comprehensive maritime security system and integrating advanced technology. Even though technology provides innovative solutions, its implementation also carries various challenges, including effectiveness, accessibility, and legal considerations. A thorough evaluation is necessary to ensure the efficient application of technology in detecting and mitigating maritime crimes.